Factors associated with the number of drugs in darunavir/cobicistat regimens. - Martinez, Esteban; Negredo, Eugenia; Knobel, Hernando; Ocampo, Antonio; Sanz, José; Garcia-Fraile, Lucio; Martin-Carbonero, Luz; Lozano, Fernando; González-Doménech, Carmen María; Gutierrez, Mar; Montero, Marta; Boix, Vicente; et al. (Oxford University Press, 2019)
Background: Darunavir/cobicistat can be used as mono, dual, triple or more than triple therapy. Objectives: To assess factors associated with the number of drugs in darunavir/cobicistat regimens. Methods: A nationwide retrospective cohort study of consecutive HIV-infected patients initiating darunavir/cobicistat in Spain from July 2015 to May 2017. Baseline characteristics, efficacy and safety at 48 weeks were compared according to the number of drugs used. Results: There were 761 patients (75% men, 98% were antiretroviral-experienced, 32% had prior AIDS, 84% had HIV RNA <50 copies/mL and 88% had ≥200 CD4 cells/mm3) who initiated darunavir/cobicistat as mono (n=308, 40%), dual (n=173, 23%), triple (n=253, 33%) or four-drug (n=27, 4%) therapy. Relative to monotherapy, triple therapy was more common in men aged <50 years, with prior AIDS and darunavir plus ritonavir use, and with CD4 cells <200/mm3 and with detectable viral load at initiation of darunavir/cobicistat; dual therapy was more common with previous intravenous drug use, detectable viral load at initiation of darunavir/cobicistat and no prior darunavir plus ritonavir; and four-drug therapy was more common with prior AIDS and detectable viral load at initiation of darunavir/cobicistat. Monotherapy and dual therapy showed a trend to better virological responses than triple therapy. CD4 responses and adverse effects did not differ among regimens. Discussion: Darunavir/cobicistat use in Spain has been tailored according to clinical characteristics of HIV-infected patients. Monotherapy and dual therapy have been common and preferentially addressed to older patients with a better HIV status, suggesting that health issues other than HIV infection may have been strong determinants of its prescription.
Keywords: SIDA - Tratamiento; Infecciones por VIH - Tratamiento; Mononucleosis - Tratamiento; Agentes antivíricos; Spain; HIV; Acquired immunodeficiency syndrome; Infectious mononucleosis; Ritonavir; Viral load; Cobicistat; Darunavir; Anti-retroviral